1998
DOI: 10.1089/thy.1998.8.627
|View full text |Cite
|
Sign up to set email alerts
|

What is the Evidence of Genetic Factors in the Etiology of Graves' Disease? A Brief Review

Abstract: Graves' disease (GD) is generally thought of as a multifactorial disorder in which genetic susceptibility interacts with environmental and endogenous factors to cause disease. The importance of genetic factors is suggested by the clustering of GD within families and by a higher concordance rate for disease in monozygotic than in dizygotic twins. This has, however, recently been shown to be less pronounced than previously thought. During the last decade much effort has been put into characterization of the gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(32 citation statements)
references
References 81 publications
0
30
0
1
Order By: Relevance
“…The HLA studies in Caucasoid populations have shown an association of GD with HLA-DR3 and -B8 [5] and of HD with HLA-DR3, -4 and -5 [6]. The HLA genes which are known to be related to AITD in the Caucasian population are known to be different from the HLA genes of other racial populations.…”
Section: Introductionmentioning
confidence: 99%
“…The HLA studies in Caucasoid populations have shown an association of GD with HLA-DR3 and -B8 [5] and of HD with HLA-DR3, -4 and -5 [6]. The HLA genes which are known to be related to AITD in the Caucasian population are known to be different from the HLA genes of other racial populations.…”
Section: Introductionmentioning
confidence: 99%
“…Variable associations of HLA class II DR, DQ, and DP, especially DRB1, DQA1, and DQB1 loci, have been reported with autoimmune endocrine diseases such as type 1 DM, Addison’s disease, Graves’ disease, and Hashimoto’s thyroiditis [9,10,11,12,13,14,15,16,17,18]. Patients with APS II/III, who develop more than two autoimmune disorders, may be related to a combination of at least two closely related genes (haplotypes).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic susceptibility in combination with external factors such as smoking, viral/bacterial infection, and chemicals is believed to initiate the autoimmune response against thyroid antigens [3,8]. Graves’ disease is considered as a multifactorial disorder in which genetic susceptibility interacts with environmental and endogenous factors to cause disease [10]. …”
Section: Discussionmentioning
confidence: 99%